Adolescent anaemia its prevalence and determinants: a cross-sectional study from south Kerala, India - Soman, Sajith Kumar; Areekal, Binu; Murali, Asha Joan; Varghese, Rosin George (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is currently one of the most common and intractable nutritional problems globally. During the period of adolescence, iron requirements increase dramatically in both boys and girls resulting in a higher probability of anaemia. The objective of the study was done to find out the prevalence of anaemia among adolescent boys and girls in Ambalapuzha Taluk and to assess the scholastic performance of the anaemic and non-anaemic in the study group. Methods: The setting was different schools of Ambalapuzha Taluk and the study was cross sectional in nature. Study subjects were children studying in 5th -10th standards selected from aided, unaided and government schools. The total sample size of the study was 2789 subjects. Statistical analysis: Data was entered in Microsoft excel and was analysed using SPSS 16.0 version Results: The prevalence of anaemia in the whole population was 53.5% (C.I-51.64-55.34%). The anaemia prevalence in females was 62.0% (C.I -59.33-64.6) and in males was 46.1% (C.I -43.55-48.61). Out of the total population 0.4% were severely anaemic [male 0.3% (5) and female 0.5% (6)]. The prevalence of moderate anaemia was 3.4% [male 2.8% (41) and female 4.2% (54)] and that of mild anaemia was 49.7 [male 43% (640) and female 57.4% (746)]. The factors that were found to be significantly associated with adolescent anaemia were female gender (62% vs. 46.1%), being overweight (59.7% vs. 53.2), not taking WIFS regularly (56.5% vs. 51.8% and 28.6% among irregularly taking WIFS and regular takers) and children coming from families with monthly income less than INR 1000. Conclusions: On comparing the academic performance of anaemic and non-anaemic children it was found that the aggregate marks was significantly lower in the anaemic group (178.11 marks) compared to the non-anaemic group (217.63 marks) (p=0.001).